Growth switching, motility and application of Bdellovibrio bacteriovorus - Capeness, Michael James (2015)
Bdellovibrio bacteriovorus, is a small mono-flagellate Gram-negative delta-proteobacterium, which has a bi-phasic lifecycle, consisting of a predatory phase; in which they invade on other Gram-negative bacteria and digest the prey cell’s content to grow and septate, or host independent phase; in which they can grow and septate in media rich in amino acids as well as vitamins and cofactors. As B. bacteriovorus can kill other Gram-negative bacteria including pathogens, they have potential to be used as a ‘living antibiotic’. I have been part of this field since 2004, a time at which the first B. bacteriovorus genome (HD100) had just been sequenced and made available, and only one study into making deletion mutants had been published. During my time in this field, the research has expanded almost exponentially, with the understanding of core pathways and systems that make B. bacteriovorus so novel being highlighted and greatly understood. In addition new techniques and methodologies never before attempted in B. bacteriovorus research have been made possible and I have been lucky to be a part of this and carried out some of the work myself. In particular I have worked on the mutation and phenotype testing of genes encoding pathways for motility, prey cell lysis, B. bacteriovorus intra-cellular signalling, and bi-phasic growth switching. These advances from my work including an animal trial into the predatory nature of B. bacteriovorus have laid the foundation for its use as a novel ‘living antibiotic’ in the future.